PENGEMBANGAN SISTEM KEAMANAN UNTUK TOKO ONLINE BERBASIS KRIPTOGRAFI AES MENGGUNAKAN BAHASA PEMROGRAMAN PHP DAN MYSQL - Benni Candra; Jusuf Wahyudi; Hermawansyah Hermawansyah (Jurnal Media Infotama, 2015)
Online Shop Security System based AES Cryptography is an application in the form of an online store website that was developed to improve safety and comfort for the user. Online store security system implemented at the time of login in the form of a verification code. This online store security system restricts website access only on one specific computer so that data is more secure than those who are not responsible. Online Shop Security System based AES cryptography was developed using Adobe Dreamweaver web editor with web promgramming PHP and MySQL database server. Web design in the form of headers, banner and other web components edited using the program Adobe Photoshop image processing applications. The processing of data using SQL syntax. Results of research and testing show that the System Security Online store based AES cryptography can display information well and is user friendly both for users and administrators, and is also equipped with a security system that can improve user comfort in accessing the online store.Keywords: System, Security, Kriftografi, AES